Design and Performance Evaluation of a Very Low Flow Coefficient Centrifugal Compressor. (14th November 2013) - Wang, Yongsheng; Lin, Feng; Nie, Chaoqun; Engeda, Abraham
Abstract : Very low flow coefficient centrifugal compressors are often applied as the last stages of multistage compressors. Due to the lower volume flow rate, the flow channels in the impeller and diffuser are so narrow that friction loss becomes the main factor, which leads to lower efficiency than that of other stages in the same compressors. In addition, most of design methods are generally based on medium flow coefficient centrifugal compressors. Taking on researches on the low flow coefficient centrifugal compressors is significant and necessary. One-dimensional (1D) code, consisting of design and analysis parts, is developed in this study to provide basic geometric data and predict the entire performance of centrifugal compressor. Three-dimensional geometry of the impeller is built. CFD simulation is carried out as well to be compared with 1D prediction. With the continuous geometry adjustment, the final performance of the centrifugal compressor will be fixed once the performance discrepancy between CFD and one-dimensional code is acceptable. The details on the flow field within impeller will be presented through CFD.